2021
DOI: 10.1155/2021/5583815
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Testing of New Hydrogel Materials for Cartilage Repair: Overcoming Fixation Issues in a Large Animal Model

Abstract: Reinforced hydrogels represent a promising strategy for tissue engineering of articular cartilage. They can recreate mechanical and biological characteristics of native articular cartilage and promote cartilage regeneration in combination with mesenchymal stromal cells. One of the limitations of in vivo models for testing the outcome of tissue engineering approaches is implant fixation. The high mechanical stress within the knee joint, as well as the concave and convex cartilage surfaces, makes fixation of rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…While it is common for engineered cartilage tissue constructs to be assessed for their compressive modulus, less often reported, and a strength of this study, was the investigation of compatible fixation of biomimetic ECM constructs within a large load-bearing cartilage defect (Marchiori et al, 2019). A comparison of chondral biomaterial fixation techniques in largeanimal models by Lotz et al (2021) found that many hydrogels show promise in vitro but fail in vivo due to inadequate fixation within a chondral defect. These data further justify the importance of incorporating a viable fixation strategy early in articular-cartilage biomaterial development.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While it is common for engineered cartilage tissue constructs to be assessed for their compressive modulus, less often reported, and a strength of this study, was the investigation of compatible fixation of biomimetic ECM constructs within a large load-bearing cartilage defect (Marchiori et al, 2019). A comparison of chondral biomaterial fixation techniques in largeanimal models by Lotz et al (2021) found that many hydrogels show promise in vitro but fail in vivo due to inadequate fixation within a chondral defect. These data further justify the importance of incorporating a viable fixation strategy early in articular-cartilage biomaterial development.…”
Section: Discussionmentioning
confidence: 96%
“…Maintaining the favourable porous structure under physiological loads is essential to support proper cellular infiltration (Matsiko et al, 2014). Unlike focal chondral defects, large-area chondral defects experience greater lateral frictional forces, increasing the risk of delamination of prochondrogenic biomaterials from chondral defects (Lotz et al, 2021). Therefore, proper biomaterial fixation within a large-area chondral defect is essential to prevent delamination and promote adequate cellular infiltration for successful tissue integration (Nehrer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The recommended management of the symptomatology of knee OA consists of conservative, non-pharmacological strategies in the first instance, then the use of pharmacological therapies, and, as a last resort, surgical options [1][2][3]. The injection of viscosupplementation substances is an option prior to surgery [4]. Regarding viscosupplementation, the main compound used currently is hyaluronic acid (HA), which is presented in different formulations [5,6].…”
Section: Introductionmentioning
confidence: 99%